Comparability of Microcosm and Field Studies in Assessing Nitrogen-Fixing Bacteria's Impact on Crop Yield: A Meta-Analysis - Erick Jose; Lopez-Arredondo; Salvador Rodríguez-Zaragoza; Nathalie Cabirol; Karla Yareli Ledesma Medina (Journal of Animal and Plant Sciences, 2025)
Crop inoculation with nitrogen-fixing bacteria (NFB) has gained significant attention as a potential strategy for enhancing crop yield and reducing reliance on synthetic fertilizers. Numerous studies have investigated the interactions between NFB and various crops. Two primary methodologies have been employed to assess the effect of NFB inoculation on crop yield: field and microcosm studies. Field studies are conducted in actual agricultural settings, offering insights into crop performance under real world conditions. Conversely, microcosm studies are conducted in controlled environments, often using small-scale experimental setups, providing a cost-effective and controlled approach. However, concerns have arisen regarding the relevance and applicability of microcosm findings to natural systems. This study aimed to evaluate the comparability of crop yield outcomes resulting from NFB inoculation in both field and microcosm studies. We performed a comprehensive weighted meta-analysis encompassing a total of 78 studies and 411 observations across the following crops: wheat (Triticum aestivum L.), rice (Oryza sativa), maize (Zea mays L.), chickpea (Cicer arietinum L.), barley (Hordeum vulgare). The overall meta-analysis revealed no significant differences (P = 0.426) between the field and microcosm studies, suggesting comparable results. However, the subgroup analysis of the inoculation methods revealed differences between the study conditions for soil inoculation. Additionally, wider confidence intervals were noted in microcosm studies, suggesting caution when extrapolating the magnitude of results to field conditions. These findings have practical implications for research on crop yield enhancement through NFB inoculation, underscoring the utility of microcosm studies as accessible models while acknowledging their inherent limitations.
Keywords: nitrogen-fixing bacteria; crop yield; biofertilizer; meta-analysis; microcosm